Viruses in food and water : risks, surveillance and control - Cook, Nigel (Woodhead Publishing Limited, 2013)
Viruses can be highly infectious and can cause widespread disease outbreaks. The dangers of viral pathogens in food and waterborne illness are increasingly being recognized and viruses transferred by these vectors are currently important areas of research. The editor and contributors review the risks, surveillance and control of food and waterborne viral disease. The first section acts as an introduction to food and environmental virology while chapters in parts two and three then explore virus detection, surveillance, risk assessment and the latest understanding of virus transmission routes and methods for virus control. The conclusion discusses recent advances and possible future developments, focusing on vaccine development and emerging viruses.
Keywords: Viruses.; Food contamination.; Viral pollution of water.; Microbial contamination.; Risk assessment.; elektronické knihy; electronic books